Development and Characterization of PVDF Thin Films for pressure sensors. (2018) - Roopaa, T.S.; Narasimha Murthy, H.N.; Praveen Kumar, V.V.; Krishna, M.
Abstract: This paper reports fabrication and characterization of PVDF thin films by spin coating. Effect of PVDF, spinning speed, spinning duration and annealing temperature on β-phase, roughness and thickness of the thin films was studied using L9 Orthogonal Array. Influence of these parameters on amount of β phase was analyzed using FTIR and XRD. Experiments showed 86 % transformation of α crystals into β crystals for the parameter combination of 10 wt. % PVDF, 3000 rpm and 70°C annealing temperature. SEM studies confirmed stretching of the films at higher speeds. Poling of the films at 8 KV increased the sensitivity of the films from 2.5 to 14 pC/N. Pressure vs. voltage was studied.